Live attenuated SARS-CoV-2 vaccine OTS-228 demonstrates efficacy, safety, and stability in preclinical model - Tobias Britzke; Nico Joël Halwe; Lorenz Ulrich; Angele Breithaupt; G. Tuba Barut; Claudia Wylezich; Nadine Ebert; Bettina Salome Trüeb; Volker Thiel; Donata Hoffmann; Martin Beer; Jacob Schön (npj Vaccines)
Abstract Live attenuated vaccines (LAV) have the potential to meet all the criteria for an efficacious vaccine. In addition to providing protection against the target disease, they offer the potential to prevent transmission, provide cross-protection by stimulating humoral and cellular immunity, and allow versatility in application routes. The SARS-CoV-2 LAV candidate, OTS-228, has demonstrated excellent safety and high efficacy in preclinical models, inducing transmission-blocking immunity and providing full protection, even against variants such as Omicron BA.2, BA.5, and XBB.1.5. However, to ensure that OTS-228 has no dose-dependent side effects and to evaluate potential risk of reversion to virulence—a known general issue with live vaccines—detailed characterization of LAV OTS-228 is essential. To address this, we conducted four different experiments using Syrian hamsters, a model for moderate to severe COVID-19. A maximum dose trial confirmed the vaccine’s full attenuation and prevention of transmission, even at high doses. In addition, four intentional serial in vivo passages demonstrated the genomic stability of the vaccine and the non-infectivity of nasal washings. Furthermore, OTS-228 maintained its attenuation and immunogenicity even after 15 additional in vitro passages, providing full protection against lung infection with virulent SARS-CoV-2 strains. Finally, a low-dose experiment confirmed the high efficacy of the vaccine candidate, establishing the protective dose 50 (PD50) at less than 100 TCID50 per hamster. Our results provide strong evidence for the safety and efficacy of the LAV candidate OTS-228 and supports its potential as a safe and effective vaccine in a highly relevant preclinical model.